Outdoor stocking density in free-range laying hens: radio-frequency identification of impacts on range use. (22nd June 2016) - Campbell, D. L. M.; Hinch, G. N.; Dyall, T. R.; Warin, L.; Little, B. A.; Lee, C.
Abstract : The number and size of free-range laying hen ( Gallus gallus domesticus ) production systems are increasing within Australia in response to consumer demand for perceived improvement in hen welfare. However, variation in outdoor stocking density has generated consumer dissatisfaction leading to the development of a national information standard on free-range egg labelling by the Australian Consumer Affairs Ministers. The current Australian Model Code of Practice for Domestic Poultry states a guideline of 1500 hens/ha, but no maximum density is set. Radio-frequency identification (RFID) tracking technology was used to measure daily range usage by individual ISA Brown hens housed in six small flocks (150 hens/flock – 50% of hens tagged), each with access to one of three outdoor stocking density treatments (two replicates per treatment: 2000, 10 000, 20 000 hens/ha), from 22 to 26, 27 to 31 and 32 to 36 weeks of age. There was some variation in range usage across the sampling periods and by weeks 32 to 36 individual hens from the lowest stocking density on average used the range for longer each day ( P <0.001), with fewer visits and longer maximum durations per visit ( P <0.001). Individual hens within all stocking densities varied in the percentage of days they accessed the range with 2% of tagged hens in each treatment never venturing outdoors and a large proportion that accessed the range daily (2000 hens/ha: 80.5%; 10 000 hens/ha: 66.5%; 20 000 hens/ha: 71.4%). On average, 38% to 48% of hens were seen on the range simultaneously and used all available areas of all ranges. These results of experimental-sized flocks have implications for determining optimal outdoor stocking densities for commercial free-range laying hens but further research would be needed to determine the effects of increased range usage on hen welfare.